MENGOPTIMALKAN POTENSI BISNIS DI ERA DIGITALISASI BAGI WARGA SEGOROYOSO 1, PLERET, BANTUL DAERAH ISTIMEWA YOGYAKARTA - Muhammad Faturohman AlBashori; Susatyo Herlambang; Subandi Subandi; Endah Wening Budiningrum; Sri Wahyuning (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
The change in marketing behavior from conventional to digital is not balanced by the existence of business actors who use digital marketing, even though businesses are believed to be able to stimulate the Indonesian economy. The use of digital technology-based marketing concepts is a hope for businesses to develop into centers of economic power. Digital marketing promotional media is expected to be an effective choice for business actors in developing their business and reaching national and international markets. Conventional promotional media, which require a lot of money and are much more complicated, are no longer a main concern for business people because of digital marketing.